2015
DOI: 10.1111/bjep.12094
|View full text |Cite
|
Sign up to set email alerts
|

Can closeness, conflict, and dependency be used to characterize students’ perceptions of the affective relationship with their teacher? Testing a new child measure in middle childhood

Abstract: Background The constructs of closeness, conflict, and dependency, which are derived from attachment theory, are widely used to qualify teachers’ perceptions of relationships with individual children. Aims Our main aim was to reveal whether similar and reliable dimensions could be identified in middle childhood with a newly developed student measure Student Perception of Affective Relationship with Teacher Scale (SPARTS). Additional validity support was sought by examining gender differences and associations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 43 publications
4
94
0
4
Order By: Relevance
“…The final sample consists of 122 students (of which 55% female). We employed a self-report questionnaire to collect information regarding demographic characteristics (age, gender), quality of relationship with teachers (using the Student Perception of Affective Relationships with Teacher Scale—SPARTS, Koomen and Jellesma, 2015), problematic and prosocial behavior (Strenghts and Difficulties Questionnaire, SDQ, Goodman, 1997) and academic achievement (as the average grade across all the school subjects).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample consists of 122 students (of which 55% female). We employed a self-report questionnaire to collect information regarding demographic characteristics (age, gender), quality of relationship with teachers (using the Student Perception of Affective Relationships with Teacher Scale—SPARTS, Koomen and Jellesma, 2015), problematic and prosocial behavior (Strenghts and Difficulties Questionnaire, SDQ, Goodman, 1997) and academic achievement (as the average grade across all the school subjects).…”
Section: Methodsmentioning
confidence: 99%
“…We examined students' perceptions of the student–teacher relationship quality using the Student Perception of Affective Relationship with Teacher Scale (SPARTS; Koomen and Jellesma, 2015). It consists of 25 items investigating three dimensions, namely Closeness, Conflict, and Negative expectations.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we hypothesize that closeness will positively be associated with autonomous motivation to defend and negatively associated with extrinsic motivation to defend. Koomen and Jellesma (2015) suggest another dimension of student-teacher relationships termed negative expectations, which they define as a desire for more positive attention (e.g., students wish that their teacher would listen to them more, could spend more time with them, knew them better, and that they could talk about more things with their teacher). In their study, Koomen and Jellesma (2015) found that negative expectations were related to more emotional problems and hyperactivity/attention problems, and less prosocial behavior.…”
Section: Interaction Between Student-teacher Relationship Quality Andmentioning
confidence: 99%
“…Hamre and Pianta (2001) demonstrated that teacher-perceived conflict in kindergarten exposed children to behavioral problems in upper elementary and middle school. Koomen and Jellesma (2015) showed recently that student-perceived conflict was related to higher levels of teacher-rated hyperactivity/attention problems.…”
Section: Teacher-student Relationships and Externalizing Problemsmentioning
confidence: 99%